An 8-inch commercial aluminum nitride MEMS platform for the co-existence of Lamb wave and film bulk acoustic wave resonators. (16th March 2023) - Hsu, Tzu-Hsuan; Tung, Shao-Siang; Huang, Yan-Ming; Wu, Guan-Lin; Chang, Chin-Yu; Ho, Yens; Chen, Yung-Hsiang; Pradeep, Yelehanka; Chand, Rakesh; Li, Ming-Huang
Abstract: This work investigates a co-design approach for fundamental symmetric Lamb wave (S0 ) resonators (LWR) and film bulk acoustic wave resonators (FBAR) in a commercial 8-inch aluminum nitride (AlN) microelectromechanical system (MEMS) platform to enable multi-band operation. The platform utilizes surface micromachining to define local release cavities, providing an undercut-free solution for acoustic resonators to achieve a high quality factor ( Q ). However, being based on a standardized platform initially tailored for FBAR devices, many design considerations and trade-offs need to be investigated for the co-existence between LWR and FBAR design. Hence, to capture the optimal design window for S0 LWRs while analyzing its performance impact on existing FBARs, the electrode configuration and its thickness are thoroughly investigated by the finite element method. In this work, a 2.2 GHz FBAR, a 700 MHz S0 LWR, and a 2.19 GHz S0 Lamé LWR are demonstrated for performance evaluation across different types of devices in this platform. The measurement results revealed a baseline performance for the FBAR device with an electromechanical coupling factor ( k t 2 ) of 6.73% and Q of 3017 at 2.2 GHz, resulting in a high figure-of-merit (FoM = k t 2 ⋅ Q ) over 200. In comparison, the 700 MHz S0 LWR exhibits a high Q of 2532 as well and a k t 2 of 1.1% (FoM = 27.8), while the 2.19 GHz S0 Lamé LWR also exhibits a high Q of 1752 and a k t 2 of 2.44% (FoM = 42.7), respectively. These performance indexes are all comparable with the current state-of-the-art, revealing the excellent potential of this AlN MEMS platform being implemented for future LWR development design or even mass production.